Cost-utility analysis of 5-fluorouracil and capecitabine for adjuvant treatment in locally advanced rectal cancer - Katanyoo, Kanyarat; Chitapanarux, Imjai; Tungkasamit, Tharatorn; Chakrabandhu, Somvilai; Chongthanakorn, Marisa; Jiratrachu, Rungarun; Kridakara, Apiradee; Townamchai, Kanokpis; Muangwong, Pooriwat; Tovanabutra, Chokaew; Chomprasert, Kittisak (Journal of Gastrointestinal Oncology; Vol 9, No 3 (June 01, 2018): Journal of Gastrointestinal Oncology, 2018)
Background: Adjuvant chemotherapy at concurrent time with radiation therapy (RT) or at adjuvant time alone in locally advanced rectal cancer (LARC) is used with several regimens. The cost-utility analysis was conducted to compare administration of two 5-FU regimens and capecitabine in the aspect of provider and societal viewpoint. Methods: Stage II or III rectal cancer patients who received pre-operative or post-operative concurrent chemoradiotherapy and adjuvant chemotherapy were compared by using decision tree model between (I) 5-FU plus leucovorin (LV) for 5 days per cycle (Mayo Clinic regimen); (II) 5-FU continuous infusion (CI) for 120-h per cycle (CAO/ARO/AIO-94 protocol); (III) standard regimen of capecitabine. All probability data were extracted from landmark study. Direct medical costs were the cost from database of Drug Medical Supply Information Center, while direct non-medical cost and utility were interviewed from stage II and III rectal cancer patients. The time horizon of this study was 5 years. Incremental cost-effectiveness ratio (ICER) was the final result in this study, which determined as the numerator of the difference of costs among three drug regimens, and the difference of quality-adjusted life years (QALYs) from each drug was the denominator. Results: 5-FU plus LV was the cheapest and least efficacy for adjuvant treatment of LARC in both provider and societal viewpoint. In provider viewpoint, the ICERs of 5-FU CI and capecitabine were 334,550 THB/QALY (US $9,840/QALY) and 189,935 THB/QALY (US $5,586/QALY), respectively, with the corresponding societal viewpoint of 264,447 THB/QALY (US $7,778/QALY) and 119,120 THB/ QALY (US $3,504/QALY) when 5-FU plus LV was used as comparator. The most influential parameter for value of treatment was acquisition cost of capecitabine. At the willingness to pay for one QALY gained in Thailand (160,000 THB or US $4,706), 5-FU plus LV, 5-FU CI and capecitabine had probabilities of costeffectiveness of 63%, 2% and 35%, respectively. Conclusions: Capecitabine was the most expensive regimen but produced the higher effectiveness than 5-FU plus LV and 5-FU CI. The most influential parameter in the model was acquisition cost of capecitabine.